Features and drivers of citizen participation: Insights from participatory budgeting in three European cities. Issue 2 (1st February 2023) - Manes-Rossi, Francesca; Brusca, Isabel; Orelli, Rebecca Levy; Lorson, Peter C.; Haustein, Ellen
ABSTRACT: Participatory budgeting (PB) is a relatively novel approach to the allocation of funds which allows ordinary citizens to become directly involved in how local government money is spent. This study identifies and examines the features and drivers of PB that incentivize citizen participation and the co-production of public services. Our analysis takes a fresh approach by setting PB initiatives in an innovative frame combining a paradigm of 'ideal' types of PB and their diachronic constituent phases. The results provide insights for both scholars and policy makers on the key features and drivers of citizen participation through PB.